الاستراتيجيات الاتصالية للعلاقات العامة في إدارة صورة المؤسسة عبر الفايسبوك أثناء أزمة كورونا -تجربة شركة الخطوط الجوية الجزائرية أنموذجا- - داودي, وداد (جامعة الوادي - University of Eloued, 2022)
جاءت هذه الدّراسة من أجل الكشف عن أهم الاستراتيجيات الاتصالية التي تنتهجتها العلاقات العامة لإدارة صورة المؤسسة عبر الفايسبوك في خضم أزمة كورونا هذه الأزمة العالمية التي مست جميع القطاعات والمؤسسات، وقد تم التطبيق على شركة الخطوط الجوية الجزائرية على اعتبار أنها من أهم الشركات المتضررة بعد إجراءات البروتوكول الصحي وغلق الحدود. وتعد هذه الدراسة من الدراسات الوصفية التي استخدمت المنهج المسحي بشقيه الوصفي والتحليلي وأداة تحليل المضمون من أجل وصف وتحليل منشورات صفحة الفايسبوك لشركة الخطوط الجوية الجزائرية شكلا ومضمونا خلال الفترة الممتدة من 25 مارس 2020 إلى 25 جانفي 2021 ، وتحديد الاستراتيجيات الاتصالية التي ركزت عليها هذه المضامين لإدارة صورة الشركة، وقد توصلت الدراسة إلى جملة من النتائج أهمها أن شركة الخطوط الجوية الجزائرية تعتمد على الإعلام أكثر من الحوار في تنفيذ استراتيجياتها الاتصالية، كما تعمد إلى تقديم المعلومات والنصائح التوعوية الداعية إلى ضرورة توخي الحذر والتزام التدابير الوقائية. This study came to reveal the most important communication strategies adopted by public relations to manage the image of the institution via Facebook during the Corona crisis, this global crisis that affected all sectors and institutions, and it wasapplied to the Algerian Airlines company as it is one of the most important companies affected after the procedures of the health protocol and the closure of the border. This study is considered one of the descriptive studies that used the survey method, both descriptive and analytical, and the content analysis tool in order to describe and analyze the Facebook page publications of the Algerian Airlines company in form and content during the period from March 25, 2020 to January 25, 2021, and to identify the strategies that focused on these contents to manage The image of the company, and the study reached a number of results, the most important of which is that the Algerian Airlines company relies on the media more than dialogue in implementing its communication strategies. It also provides information and educational advice calling for the need to be careful and adhere to preventive
Communication strategies for public relations in managing the image of the institution via Facebook during the Corona crisis -The Air Algerie experience as a model-
مقال
Keywords: الاستراتيجيات الاتصالية للعلاقات العامة ، أزمة كورونا ، إدارة صورة المؤسسة ، الفايسبوك ، شركة الخطوط الجوية الجزائرية; communication strategies for public relations, corona crisis, enterprise image management, Facebook, the Algerian Airlines company